Degree of certainty in scientific advice: implications for risk management and communication: Event report on a training workshop on uncertainty with risk managers. Issue 7 (13th July 2022) - ,; Sahlin, Ullrika; Hart, Andy; Zilliacus, Johanna
Abstract: As part of its commitment to transparency, the European Food Safety Authority (EFSA) has been developing improved approaches to assessing uncertainty and expressing the degree of certainty in its scientific outputs. The objectives of this workshop were to review and improve the provision of this information by EFSA and its usefulness for risk managers, and to help risk managers to interpret and use it in their work. The workshop focussed on the non‐regulated areas of EFSA's work, chemical contaminants and biological hazards in food, plant health and animal health and welfare, and was attended by a total of 76 participants, of whom 28 were from DG SANTE and 22 were risk managers from EU Member State institutions. The workshop was held over two half days, one day focussed on uncertainty and decision‐making and the other on uncertainty and communication. Each session began with an invited presentation by an eminent external speaker and an EFSA presentation on its approach, followed by separate breakout discussions for the four areas of EFSA's work. Results from the breakout sessions were then presented and discussed in plenary. The workshop concluded with closing remarks from DG SANTE and EFSA, highlighting nine main points emerging from the discussions.